KEMAMPUAN SELF REGULATED LEARNING (SRL) MAHASISWA CALON GURU SEKOLAH DASAR DALAM HYBRID LEARNING DI UNIVERSITAS PGRI SEMARANG - Yoyok Haryono; Joko Siswanto; Sumarno (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
The purpose of this study was to determine the ability of Self Regulated Learning (SRL) for prospective elementary school teaching students in hybrid learning. This research method uses a qualitative approach with data collection techniques carried out through observation, interviews, and documentation. The research focus is on Self Regulated Learning (SRL) students of elementary school teacher candidates at PGRI University Semarang in 2022. The subjects in this study were student prospective teachers of Elementary School Teacher Education (PGSD), consisting of 4 students who had been selected based on their level of achievement which had been categorized. The results of the study were in the initial SRL questionnaire distribution there were student elementary school teacher candidates who had a high SRL level of 64% for 49 students, and a moderate SRL level of 36% for 88 students. There were findings that there were no student elementary school teacher candidates with a low SRL category. The results of interviews with 4 subjects showed consistency in su subject in every aspect from planning to reflection, so that the subject is by the aspects of Self Regulated Learning.